2021
DOI: 10.1152/jn.00184.2021
|View full text |Cite
|
Sign up to set email alerts
|

A novel gain-of-function sodium channel β2 subunit mutation in idiopathic small fiber neuropathy

Abstract: Small fiber neuropathy (SFN) is a common condition affecting thinly myelinated Aδ and unmyelinated C fibers, often resulting in excruciating pain and dysautonomia. SFN has been associated with several conditions, but a significant number of cases have no discernible cause. Recent genetic studies have identified potentially pathogenic gain-of-function mutations in several the pore-forming voltage-gated sodium channel α subunits (NaVs) in a subset of patients with SFN, but the auxiliary sodium channel β subunits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Na V channels are composed of a pore-forming a subunit (Na V 1.1-1.9) and associated b subunits (Na V b 1-4), which modulate various aspects of Na V function and neuronal excitability (O'Malley and Isom, 2015; Alsaloum et al, 2019Alsaloum et al, , 2021. Thus, we Figure 6.…”
Section: Depolarizing Voltage Pulses the Conductance-voltage (G-mentioning
confidence: 99%
“…Na V channels are composed of a pore-forming a subunit (Na V 1.1-1.9) and associated b subunits (Na V b 1-4), which modulate various aspects of Na V function and neuronal excitability (O'Malley and Isom, 2015; Alsaloum et al, 2019Alsaloum et al, , 2021. Thus, we Figure 6.…”
Section: Depolarizing Voltage Pulses the Conductance-voltage (G-mentioning
confidence: 99%
“…A recent Brazilian study using WGS identified two new mutations 50. Very rarely, patients have pathogenic variants in the auxiliary beta, rather than the alpha, sodium channel subunits or loss-of-function variants associated with reduced pain sensitivity that can be lethal 59 60. Two cases harbouring new SCN9A variants with neuropathic pain and biopsy-proven small fibre neuropathy appeared to respond to intravenous immunoglobulin administered pretesting,61 though it is uncertain if this was coincidental.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…VGSCs comprise a pore-forming α subunit, which is associated with auxiliary β subunits. Among the nine different VGSCs (Nav1.1-Nav1.9) expressed in humans, Nav1.9, Nav1.8, and Nav1.7, encoded by SCN11A, SCN10A, and SCN9A, respectively, have been genetically and functionally validated as drivers of chronic pain in humans [2,3]. The biophysical properties of the three VGSCs determine nociceptor excitability; therefore, a gain-of-function or changed expression can lead to neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%